The good, the bad and the ugly: Taking stock of Europe's new trade policy strategy - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2021)
This Policy Brief takes stock of the EU Trade Policy Review - the Commission's proposed strategy for trade. Despite appearances, the Review doesn't come close to its billing as a strategy for the new geopolitics of trade. In fact, the Review is weak on key geopolitical developments and rather gives the impression that the EU doesn't have an ambition to shape outcomes. Obviously, the Review is anchored in Europe's general economic climate: defensiveness on globalization, competition and digitalization. It follows that Europe is getting increasingly detached from world developments.
Keywords: 330; EU-Außenwirtschaftspolitik; EU-Staaten